The Effect of Tax Avoidance and Tax Risk on Company Value in Manufacturing Companies Listed on the IDX Period 2019-2023 - Khusnaini, Tita Dara; Adhim, Chairul; Ramadhan, Risca Arisca (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study is intended to reveal how Tax Risk, Tax Avoidance affect Firm Value in the Manufacturing industry listed on the IDX from 2019 to 2023. The purposive sampling method is the method used in sampling, which includes a total of 320 companies and 1,600 data on financial statements. To analyze the data, the control panel regression method was used with STATA 15 software. But the findings do not show a real impact of tax avoidance on firm value. Instead, tax risk is shown to positively influence and have a significant impact on firm value, indicating that firms can utilize tax risk to increase their value. The results suggest that managing corporate tax risk is more important than just trying to avoid taxes.